Optimasi Penyetelan Celah Katup Terhadap Emisi Gas Buang Pada Sepeda Motor Matic - Muhammad Sulaeman; Mulyadi (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2022)
The development of the number of motorized vehicles in Indonesia is increasing rapidly every year, most motorized vehicles can produce bad exhaust emissions, either due to inadequate maintenance or bad driver behavior. Air pollution that has occurred so far is largely due to the presence of motorized vehicles as a means of transportation. Most of the air pollution is caused by motor vehicle emissions. Motor vehicles emit harmful gases which can have a negative impact, both on human health and the environment. This research method is experimental with a research data collection design namely Optimization of valve clearance adjustments on vehicles, then the results of the settings that have been observed with differences in valve clearance adjustments with lower exhaust emissions of CO and HC. This research was then given the treatment of setting the IN valve gap 0.03mm, 0.04mm, 0.05mm 0.06mm, 0.07mm, 0.08mm, 0,09mm and the EX valve; 0.05mm, 0.06mm, 0.07mm, 0.08mm, 0.09mm, 0.10mm, 0,11mm at each rotation of 900rpm and 2000rpm, 2100rpm. With the aim of knowing the characteristics of the exhaust gas that comes out of the vehicle into the environment. With the experimental results of optimizing the IN valve gap of 0.04mm, the EX valve 0.06mm gets 0.04% CO, 28 ppm HC, 900rpm rotation. At 2000rpm it gets CO 0.09%, HC 26ppm. 2100rpm CO 0,33%. HC 44ppm. Referring to the Regulation of the Minister of Environment Number: 05 of 2006, it can be concluded that the exhaust emissions resulting from optimization are categorized as environmentally friendly.